KAJIAN TIMBULAN SAMPAH BAHAN BERBAHAYA DAN BERACUN (B3) RUMAH TANGGA DI KELURAHAN SENDANGMULYO KECAMATAN TEMBALANG KOTA SEMARANG - Nenti Diah Kusuma Prasetyaningrum; Tri Joko; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
The absence of a regulation that specifically regulates household hazardous waste makes its management neglected in the community. Sendangmulyo village is a village with high population and various activities. To find out the characteristics and characteristics of  household hazardous waste in Sendangmulyo Village, the researcher uses observational method with cross sectional approach. The population of this study is all households in TPS Klipang Sendangmulyo with sample 97 KK. The results of this study indicate that the average of household waste generated hazardous is 0.099 kg/o/ h or 0.057 l/o/bln, with a high income level of 0.121 kg/o/ h or 0.066 l/o/ bln, while 0.077 kg/o/ h or 0.051 l/o/ bln, and low 0.071 kg/o/ h or 0.048 l/o/ bln. The characteristics of generated generation are easily explosive (29.15%), corrosive (21.67%), toxic (35.74%), irritating (13.40%) and infectious (0.04%). All of respondents (100%) not already have a good knowledge about household B3 waste and 100% of respondents also have not done household hazardous waste storage in accordance with not sorting with domestic waste and container according to the characteristics. The waste generation of household waste in Sendangmulyo Village is mostly toxic (35.74%).